Cathodic generation of reactive (phenylthio)difluoromethyl species and its reactions: mechanistic aspects and synthetic applications - Iwase, Sadanobu; Inagi, Shinsuke; Fuchigami, Toshio (Beilstein Journal of Organic Chemistry, 2022)
The cathodic reduction of bromodifluoromethyl phenyl sulfide (1) using o-phthalonitrile as a mediator generated the (phenylthio)difluoromethyl radical, which reacted with α-methylstyrene and 1,1-diphenylethylene to provide the corresponding adducts in moderate and high yields, respectively. In contrast, chemical reduction of 1 with SmI2 resulted in much lower product yields. The detailed reaction mechanism was clarified based on the cathodic reduction of 1 in the presence of deuterated acetonitrile, CD3CN.
Keywords: bis(phenylthio)difluoromethane; cathodic reduction; deuteration; o-phthalonitrile mediator; (phenylthio)difluoromethylation; (phenylthio)difluoromethyl radical